Rethinking Financial Inclusion: From Access to Autonomy - Hulikal Muralidhar, Srihari; Bossen, Claus; O'Neill, Jacki (Journal of Computer-Supported Cooperative Work, 2019)
Financial inclusion has been defined and understood primarily in terms of access, thereby constituting ‘inclusion’/’exclusion’ as a binary. This paper argues such a view to be myopic that risks treating financial inclusion as an end in itself, and not as means to a larger end. ‘Access’ oriented perspectives also fail to take into account considerations of structural factors like power asymmetries and pay inadequate attention to user practices. Through the case of auto-rickshaw drivers in Bangalore, India, and their use of Ola, a peer-to-peer taxi hailing service similar to Uber, we show that access is a necessary, but not sufficient condition to achieve financial inclusion in a substantive sense. By examining in detail, the financial needs and practices of rickshaw drivers, we identify the opportunities and constraints for digital technology to better support their financial practices and enhance their wellbeing. The paper proposes adding ‘autonomy’ and ‘affordances’ as two crucial factors to be included in the discourse on financial inclusion. Finally, we outline design implications for P2P technologies to contribute towards the financial inclusion of drivers.